Kitab Yeremia: Penyesalan dan Pertobatan, Harapan dan Pengharapan, serta Keadilan dan Hukuman - Buyung Salendra Tandiawo (Voice, 2024)
This article is an in-depth commentary on the Book of Jeremiah. It discusses in detail the historical and cultural context in which the Book of Jeremiah was written, and explores the meaning and application of its messages. In this writing, the author reveals the historical background against which the Book of Jeremiah was written. It also reviews the messages contained in the Book of Jeremiah, such as regret and repentance, hope and expectation, justice and punishment. The author explores the meaning and implications of these messages, inviting readers to reflect on and apply the teachings contained in the Book of Jeremiah to their daily lives. It provides a deeper understanding of the Book of Jeremiah, relates the prophet Jeremiah's messages to the historical and cultural context of the time, and invites readers to reflect on and apply these teachings in their daily lives.